The evaluation of biochemistry practicum based on several parameters of laboratory services in chemistry department Universitas Negeri Surabaya during the even semester - Mirwa Adiprahara Anggarani; Dzikra Nasyaya Mahfudhah; Soesilowati Soesilowati; Avissa Auryn Wijayanti; Syananda Zahra Fadila; Nuniek Herdyastuti; Muhammad Nurrohman Sidiq (Pascasarjana Universitas Negeri Medan, 2023)
This study was conducted to evaluate laboratory management during biochemistry practicum activities and to build laboratory information for the internal and external community of Universitas Negeri Surabaya (Unesa) in 2023 through several aspects, namely infrastructure, tools, materials, and PLP/laboratory services. A descriptive-qualitative approach is used with a questionnaire for all biochemistry practitioners. The result shows that all aspects of biochemistry practicum activities obtain percentages sequentially of 89%, 90%, 93%, and 90%, which are included in the excellent category, so it can be concluded that all practitioners are highly satisfied with laboratory services during practicum. However, improvements to the deficiencies still need to be made so that the following practicum activities run better and optimally.Keywords: Biochemistry practicum; Evaluation; Laboratory management; Laboratory services